2010
DOI: 10.1371/journal.pone.0014026
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic, Large-Scale Profiling of Transcription Factor Activity from Live Cells in 3D Culture

Abstract: BackgroundExtracellular activation of signal transduction pathways and their downstream target transcription factors (TFs) are critical regulators of cellular processes and tissue development. The intracellular signaling network is complex, and techniques that quantify the activities of numerous pathways and connect their activities to the resulting phenotype would identify the signals and mechanisms regulating tissue development. The ability to investigate tissue development should capture the dynamic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 63 publications
0
36
0
Order By: Relevance
“…To further examine the impact of CDKi on EMT related events we used a novel transcription factor (TF) reporter cell array 21,22,31 and found that CDK2i treatment of TNBC cells led to an early increase in activity of b-catenin, Smad3, Snail, Sp1, Twist, YY1, and Zeb1 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To further examine the impact of CDKi on EMT related events we used a novel transcription factor (TF) reporter cell array 21,22,31 and found that CDK2i treatment of TNBC cells led to an early increase in activity of b-catenin, Smad3, Snail, Sp1, Twist, YY1, and Zeb1 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 After treating MDA-MD-231 cells with control or CDK2i, activities of 11 TFs associated with oncogenesis were measured at several time points. Factors selected for study were based on association with proliferation, apoptosis, and metastasis ( Table 2).…”
Section: Characterization Of Signaling Changes In Mda-mb-231 Cells Afmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] However, due to low transfection efficiencies, acquiring stably transfected cells requires long-term drug selection limiting the application of this approach to cell lines as opposed to primary cells. Also, the transient nature of transfection makes it difficult to follow cells for a long time (days to weeks) as required for stem cell differentiation.…”
Section: Introductionmentioning
confidence: 99%